President Prabowo’s Education Policy in News Text: A Critical Discourse Analysis of Kompas.id - Miranda Kristin Lumban Tungkup; Marino Sihombing; Sarah Priscilla Silitonga; Partohap Saut Raja Sihombing (Jurnal Sosial Humaniora dan Pendidikan, 2026)
Education policy has become a prominent site of public discourse in Indonesia, particularly in relation to poverty reduction and social inequality. This study investigates the discursive construction of President Prabowo Subianto’s People’s Schools (Sekolah Rakyat) policy as represented in the Compas.id news article “Prabowo Inaugurates 166 People’s Schools. How is Their Education Managed?” published in January 2026. Adopting a descriptive qualitative design within a critical paradigm, the research employs Norman Fairclough’s three-dimensional Critical Discourse Analysis framework, encompassing textual features, discursive practices, and socio-cultural contexts. The analysis reveals that the news discourse predominantly represents the state as a moral and authoritative agent committed to social justice and national development, while framing People’s Schools as a humanitarian solution to structural poverty. Linguistic choices and narrative strategies tend to legitimize government authority and foreground benevolent intentions, whereas critical issues related to legal status and institutional integration within the National Education System receive limited emphasis. This research contributes to critical media and education policy studies by highlighting the role of news discourse in shaping public understanding of state-led educational reforms in Indonesia.